Interactive control algorithm based on real-time solar irradiance forecasting model for standalone photovoltaic system - Mohd Shah, Ahmad Syahiman; Azri, Idris; Jadin, Mohd Shawal; Mohd Rashid, Muhammad Ikram; Mohd Saifizi, Saidon (2019)
Standalone photovoltaic (PV) system is practical and beneficial for the place where the physical power transmission line is not feasible. Nevertheless, for miniature scale standalone PV system, efficient and interactive energy management is extremely necessary to ensure that the battery is capable of supplying energy to the load uninterruptedly without any failure as its condition is being monitored, time by time. In this paper, a real-time energy management system equipped with wireless monitoring features has been developed and tested. All energy information such as battery voltage, generating current, discharging current, etc. are well displayed and extracted directly from the developed system. The high-power switching system is able to be controlled remotely as several MOSFETs attached to the main circuit are feasible to be flagged on or off via Blynk application instantaneously without any time lags. Therefore, the proposed system may become a good model for better small-storage-capacity based real-time energy management system in the future.